MiR-143/145 deficiency attenuates the progression of atherosclerosis in Ldlr-/- mice - Sala, Federica; Aranda, Juan F.; Rotllan, Noemi; Ramírez, Cristina M.; Aryal, Binod; Elia, Leonardo; Condorelli, Gianluigi; Catapano, Alberico Luigi; Fernández-Hernando, Carlos; Norata, Giuseppe Danilo (Thrombosis and Haemostasis, 2014)
The miR-143/145 cluster regulates VSMC specific gene expression, thus controlling differentiation, plasticity and contractile function, and promoting the VSMC phenotypic switch from a contractile/non-proliferative to a migrating/proliferative state. More recently increased miR-145 expression was observed in human carotid atherosclerotic plaques from symptomatic patients. The goal of this study was to investigate the contribution of miR-143/145 during atherogenesis by generating mice lacking miR-143/145 on an Ldlr-deficient background. Ldlr-/- and Ldlr-/--miR-143/145-/- (DKO) were fed a Western diet (WD) for 16 weeks. At the end of the treatment, the lipid profile and the atherosclerotic lesions were assessed in both groups of mice. Absence of miR-143/145 significantly reduced atherosclerotic plaque size and macrophage infiltration. Plasma total cholesterol levels were lower in DKO and FLPC analysis showed decreased cholesterol content in VLDL and LDL fractions. Interestingly miR-143/145 deficiency per se resulted in increased hepatic and vascular ABCA1 expression. We further confirmed the direct regulation of miR-145 on ABCA1 expression by qRT-PCR, Western blotting and 3′UTR-luciferase reporter assays. In summary, miR-143/145 deficiency significantly reduces atherosclerosis in mice. Therapeutic inhibition of miR-145 might be useful for treating atherosclerotic vascular disease.
Keywords: miR-143/145; atherosclerosis; ABCA1; smooth muscle cells